Challenges experienced by community health workers and their motivation to attend a self-management programme - Levona J. Johnson; Laura H. Schopp; Firdouza Waggie; José M. Frantz (AOSIS, 2022)
Background: Community health workers (CHWs) are change agents expected to assist in decreasing the global burden of disease in the communities they serve. However, they themselves have health risk behaviours, which predispose them to non-communicable diseases and thus need to be empowered to make better health choices. There is a gap in literature detailing the challenges faced by CHWs in addressing their own health risk behaviours. Aim: This study aimed to explore the challenges experienced by CHWs in carrying out their daily duties and the motivating factors to join a self-management programme. Setting: The study was conducted in a low socio-economic urban area of the Western Cape, South Africa. Methods: This study used a qualitative exploratory design using in-depth interviews to obtain rich data about the personal and professional challenges that CHWs experience on a daily basis. Results: Five themes emerged with regard to professional challenges (social conditions, mental health of patients, work environment, patient adherence and communication). This cadre identified ineffective self-management as a personal challenge and two themes emerged as motivation for participating in a self-management programme: empowerment and widening perspective. Conclusion: The challenges raised by the CHWs have a direct impact on their role in communities. This study therefore highlights an urgent need for policymakers and leaders who plan training programmes to take intentional strategic action to address their health challenges and to consider utilising a self-management intervention model to improve their overall health status.